Stability analysis of positive switched systems via joint linear copositive Lyapunov functions. (February 2016) - Sun, Yuangong
Abstract: In this paper, we study the asymptotic stability of continuous-time positive switched linear systems for the case when each subsystem is only stable. By using the so-called "joint linear copositive Lyapunov function" (JLCLF) generalizing the common linear copositive Lyapunov function, we show that the system remains asymptotically stable under appropriate switching if it has a JLCLF. Then, the main result is extended to positive switched linear systems with time delay.